Motivasai Keputusan Implementasi PSAK 73 Pada PT X - Shauki, Elvia R.; Mustofa, Najib (Politeknik Ganesha Medan, 2024)
This research aims to evaluating policy making for implementing PSAK 73 in companies in Indonesia, based on PT X which is there will still be problems that arise until 2022. The implementation of PSAK 73, which began in 2020, forced companies in Indonesia to adjust their lease contracts and calculations related to their leases. The significant change from PSAK 30 to PSAK 73 has caused a lot of confusion and errors in its application at PT X especially at its branch offices. A qualitative case study method approach with multiple embedded unit analysis using documentation, observation and semi-structured interview data. This research uses content analysis, thematic analysis, and constant comparison using NVivo 12 Plus software. Institutional logics is relevant in explaining the relationship between individual behavior and institutions that can influence an action. The results of the study show that symbolic carriers (PSAK 73) affect material carriers (actor, routines, artifacts, and procedures) thereby triggering the coupling practice in preparation of SOPs referring to PSAK 73 and the decoupling practice occurred when there are problems that are not stated in the regulations so the company makes adjustments. There are multiple logics including the logic of actors, routines, artifacts and procedures. The competing logics are logic of procedures and actors in adjustment of lease management conditions. Procedure logics is the dominant logic that is the reference of lease management. PT X need to design more appropriate policies taking into account company behavior